Generic Technique for Explicit Definition of Models with SPT Phases - Topchyan, H.
This paper focuses on creation of a technique to derive systems with explicitly defined symmetry protected topological (SPT) phases on a triangular lattice, based on models featuring arbitrary symmetries. It results in emergence of effective edge models, which are massless in non-trivial SPT phases. When applied on non-interacting systems, the technique results in models with a translational invariance, which ensures independence from the local geometry.
Keywords: Physics